Case Report: Whole-exome sequencing identified two novel COMP variants causing pseudoachondroplasia - Zhou, Lin; Chen, Jing; Liu, Qian; Yang, Shuting; Xie, Wanqin; Peng, Ying (Frontiers in Endocrinology, 2023)
Pseudoachondroplasia (PSACH) is a rare, dominant genetic disorder affecting bone and cartilage development, characterized by short-limb short stature, brachydactyly, loose joints, joint stiffness and pain. The disorder is caused by mutations in the COMP gene, which encodes a protein that plays a role in the formation of collagen fibers. In this study, we present the clinical and genetic characteristics of PSACH in two Chinese families. Whole-exome sequencing (WES) analysis revealed two novel missense variants in the COMP gene: NM_000095.3: c.1319G>T (p.G440V, maternal) and NM_000095.3: c.1304A>T (p.D435V, paternal-mosaic). Strikingly, both the G440V and D435V mutations were located in the same T3 repeat motif and exhibited the potential to form hydrogen bonds with each other. Upon further analysis using Missense3D and Pymol, we ascertained that these mutations showed the propensity to disrupt the protein structure of COMP, thus hampering its functioning. Our findings expand the existing knowledge of the genetic etiology underlying PSACH. The identification of new variants in the COMP gene can broaden the range of mutations linked with the condition. This information can contribute to the diagnosis and genetic counseling of patients with PSACH.